Statistical Evaluation of the Earned Value Forecasts Simulated with System Dynamics Model - Tomasz PROTASOWICKI; Jerzy STANIK (Communications of International Proceedings, 2021)
The work describes the concept of assessing the adequacy of a simulation model based on the System Dynamics framework. The first part of paper presents the characteristics of the Earned Value, the System Dynamics method, and the nature of the problem of assessing the adequacy of the simulation model built on its assumptions. The second part provides the methods proposed by the authors to determine the adequacy of the System Dynamics model, the Earned Value simulation model which is a subject of study as well as results of the experiment conducted on the basis of this model.
Keywords: Simulation; System Dynamics; Earned Value Method; Project Management.